REVITALISASI KESENIAN KOROMONG MELALUI PEMBUATAN BUKU ANAK - Sopian, Rahmat; Ruhimat, Mamat; Meganova Lyra, Hera (Midang, 2025)
The Community Service Program (PPM) is one of the Tri Dharma (three pillars) and an integral part of education and research for lecturers. At Padjadjaran University, one effort to optimize and regenerate PMM is by collaborating PPM with Student Study Service (KKN). This project was carried out by lecturers from the Faculty of Cultural Sciences and students of Padjadjaran University in Sukahayu Village, Rancakalong District, Sumedang Regency, with a focus on revitalizing the traditional art of Koromong. As a local cultural heritage, Koromong has been facing a decline due to reduced youth interest and limited documentation. The program aimed to revive this art through an educational approach by developing a children’s book titled “Jelajah Nada Ceria Koromong” ‘Exploring the Cheerful Melody of Koromong’. The book, designed as an illustrated story, introduces the history, instruments, costumes, and cultural values of Koromong in a way that is accessible to elementary students. The results indicate an increase in students’ understanding and appreciation of local arts, along with greater community awareness of cultural preservation. Collaboration among lecturers, students, traditional artists, educators, and the village government contributed to the program’s success. The team further recommends the digitalization of the book and documentation of Koromong performances to ensure long-term accessibility and sustainability in promoting cultural literacy in the digital era.